Enhancement of chlorpromazine efficacy in breast cancer treatment by 266 nm laser irradiation - Ana Maria Udrea; Angela Staicu; Adriana Smarandache; Ionut Relu Andrei; Madalina Andreea Badea; Speranta Avram; Mihail Lucian Pascu; Ruxandra Angela Pirvulescu; Mihaela Balas (Scientific Reports)
Abstract Breast cancer remains a global health challenge, prompting interest in the anticancer properties of other drugs, including chlorpromazine (CPZ). This study presents a novel approach in breast cancer treatment using laser irradiated CPZ. CPZ dissolved in distilled water, was exposed to 266 nm laser irradiation for varying durations, characterized by UV-Vis and FTIR spectroscopy, followed by drug-likeness and ADME-Tox predictions. In vitro assays evaluated the cytotoxicity and cellular effects on MCF-7 breast cancer cells, and compared with MCF-12 A healthy cell line. Laser irradiation altered CPZ molecular structure resulting in photoproducts with favourable drug-like properties and ADME-Tox profiles. In vitro evaluations demonstrate dose and irradiation time-dependent cytotoxicity against breast cancer cells, and reduced toxicity on healthy cell line. Significant alterations in F-actin organization, and excessive ROS generation were also proved, suggesting the potential of laser-modified CPZ for breast cancer therapy. This study introduces a novel approach to breast cancer treatment through laser irradiated CPZ, highlighting promising advancements in therapy and emphasizing the role of laser-generated compounds.